Monkey in the Self-Portrait – The Non-Human Animal and the Question of Self-Representation - Tiina Salmia (Filmiverkko ry, 2022)
The article examines self-portraits taken in 2011 by Indonesian crested black macaque monkey Naruto with wildlife photographer David Slater’s camera. People for the Ethical Treatment of Animals (PETA) filed a lawsuit against Slater to request that the monkey be assigned copyright and that PETA be appointed to administer proceeds from the photos for the benefit of Naruto and crested macaques in the reserve on Sulawesi. With this provocative lawsuit PETA wanted to stimulate discussion about expanding legal rights for non-human animals. These photographs, the discussion concerning them, and the court case shed light on the embodied agency of a non-human animal and human-animal relations in visual culture. In this article, I examine what it means when an animal points a camera at himself and takes a picture. I argue that the knowledge that the picture of the monkey is taken by the monkey himself causes the picture to be seen in a new light and raises questions as to the animal’s status as an object and an Other. Furthermore, it urges a thorough re-examine of the agency, power, and embodied consciousness associated with photography and the practices of self-representation.